Tinjauan Etis-Teologis Terhadap Euthanasia Pasif di GMIST Jemaat Torsina Mulengen - Sihombing, Daniel Chandra William; Rey, Bryant Marsellino Yoseph (Peneliti.net, 2024)
Euthanasia is a medical term that is understood to mean death that occurs due to situations and conditions that do not allow a person to continue living or to surrender to the situation that has occurred. In practice, euthanasia experiences various kinds of controversy both globally and domestically. This article tries to review and then make ethical and theological decisions regarding the existing Passive Euthanasia Act.